Differences in augmented reality games performance between individuals with down syndrome and individuals with typical development - de Almeida Barbosa R.T. (2023)
© The authors (2023), this article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated.Introduction: Down syndrome is the most common genetic cause of intellectual disability, and the use of augmented reality can be improving the cognitive, motor, and literacy skills of this population. Objective: to compare statistical differences in learning between individuals with Down syndrome and individuals with typical development using augmented reality games. Methods: we compared the reaction time before and after the virtual reality tasks, in addition to the performance in these tasks, which consisted of correctly identifying numbers and letters in 46 people with Down syndrome and 46 controls with typical development. Results: our results indicate that the total points for the typical development group were higher (M = 13.0 and 11.9) when compared to the Down syndrome group (M = 6.6 and 4.6) for letters of the alphabet and numbers, respectively. Furthermore, the results indicated that participants in both groups were more accurate in identifying alphabetic symbols when compared to numerical symbols, and both groups were sensitive to the number of symbols presented in each phase. The down syndrome group had a lower performance when compared to the typical development group. Conclusion: despite the need for further studies, our results support the outcome that there is clinical utility of an intervention based on virtual reality tasks for people with Down syndrome. In conclusion, the use of this technology to improve the reaction time of this population is considered useful.